Relative stopping power measurements to aid in the design of anthropomorphic phantoms for proton radiotherapy - Grant, Ryan L. (J Appl Clin Med Phys, 2014)
The delivery of accurate proton dose for clinical trials requires that the appropriate conversion function from Hounsfield unit (HU) to relative linear stopping power (RLSP) be used in proton treatment planning systems (TPS). One way of verifying that the TPS is calculating the correct dose is an end‐to‐end test using an anthropomorphic phantom containing tissue‐equivalent materials and dosimeters. Many of the phantoms in use for such end‐to‐end tests were originally designed using tissue‐equivalent materials that had physical characteristics to match patient tissues when irradiated with megavoltage photon beams. The aim of this study was to measure the RLSP of materials used in the phantoms, as well as alternative materials to enable modifying phantoms for use at proton therapy centers. Samples of materials used and projected for use in the phantoms were measured and compared to the HU assigned by the treatment planning system. A percent difference in RLSP of 5% was used as the cutoff for materials deemed acceptable for use in proton therapy (i.e., proton equivalent). Until proper tissue‐substitute materials are identified and incorporated, institutions that conduct end‐to‐end tests with the phantoms are instructed to override the TPS with the measured stopping powers we provide. To date, the RLSPs of 18 materials have been measured using a water phantom and/or multilayer ion chamber (MLIC). Nine materials were identified as acceptable for use in anthropomorphic phantoms. Some of the failing tissue substitute materials are still used in the current phantoms. Further investigation for additional appropriate tissue substitute materials in proton beams is ongoing. Until all anthropomorphic phantoms are constructed of appropriate materials, a unique HU‐RLSP phantom has been developed to be used during site visits to verify the proton facility's treatment planning HU‐RLSP calibration curve. PACS number: 87.53.Bn